A Neonate with Autosomal Dominant Pseudohypoaldosteronism Type 1 Due to a Novel Microdeletion of the NR3C2 Gene at 4q31.23 - Su Jin Kim; Dasom Park; Woori Jang; Juyoung Lee (Children, 2021)
Dehydration with hyponatremia can occur from a variety of causes and can be potentially fatal to infants. Pseudohypoaldosteronism type 1 (PHA1) is a rare disease that can cause severe dehydration along with hyponatremia and hyperkalemia because of renal tubular unresponsiveness to mineralocorticoids. Autosomal dominant PHA1 (ADPHA1, OMIM #177735) is caused by inactivating mutations in the NR3C2 gene, which encodes the mineralocorticoid receptor, and it can lead to renal salt-wasting, dehydration, and failure to thrive during infancy. Here, we report a case of a 20-day-old female neonate who presented as severe dehydration with hyponatremia and polyuria. We suspected that her diagnosis might be PHA1 based on markedly elevated plasma renin activity and serum aldosterone levels. For the genetic diagnosis of PHA1, we performed targeted exome sequencing of all causative genes of PHA1, but the result was negative. We confirmed by chromosomal microarray that a novel heterozygous microdeletion was found in the 4q31.23 region spanning exons 7–9 of the NR3C2 gene, and the patient was diagnosed with ADPHA1. In conclusion, our patient is a case of ADPHA1 that developed into a salt-wasting crisis in the neonatal period due to a microdeletion of the 4q31.23 region inherited from her father.